Corka proboszcza - Orwell, George, 1903-1950.; Drozdowski, Bohdan (Warszawa : MUZA SA, 2000)
Polish translation of "Clergyman's Daughter". A realistic, colored, forcible and at times even a brutal taale of the fate of Dorothy Hare, daughter of a provincial Anglican pastor.
Keywords: Clergy -- England -- Suffolk -- Fiction; Poverty -- England -- Suffolk -- Fiction; England -- Social conditions -- 20th century -- Fiction